Increased platelet activation in patients with stable and acute exacerbation of COPD. Issue 9 (20th April 2011) - Maclay, John D; McAllister, David A; Johnston, Shonna; Raftis, Jennifer; McGuinnes, Catherine; Deans, Andrew; Newby, David E; Mills, Nicholas L; MacNee, William
Abstract : Rationale: Chronic obstructive pulmonary disease (COPD) is associated with systemic inflammation and cardiovascular disease. Interaction between inflammatory cells and activated platelets is important in the pathogenesis of atherothrombosis and may contribute to cardiovascular risk in patients with COPD. Objectives: To assess platelet-monocyte aggregation in patients with COPD and matched controls, and in patients with an acute exacerbation of COPD. Methods: 18 men with COPD and 16 male controls matched for age and cigarette smoke exposure were recruited. A further 12 patients were investigated during and at least 2 weeks after hospitalisation for an acute exacerbation. Platelet-monocyte aggregation and platelet P-selectin expression were determined using flow cytometry. Results: Patients with COPD had increased circulating platelet-monocyte aggregates compared with controls (mean (SD) 25.3 (8.3)% vs 19.5 (4.0)%, p=0.01). Platelet-monocyte aggregation was further increased during an acute exacerbation compared with convalescence (32.0 (11.0)% vs 25.5 (6.4)%, p=0.03). Platelet P-selectin expression and soluble P-selectin did not differ between groups. Conclusions: Patients with stable COPD have increased circulating platelet-monocyte aggregates compared with well-matched controls. Platelet activation is further increased in patients with COPD during an acute exacerbation. These findings identify a novel mechanism to explain the increased cardiovascular risk in COPD and suggest platelet inhibition as a plausible therapeutic target.